PENGARUH GREEN MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK HIJAU DI RESTORAN SARI ORGANIK UBUD - Risyamuka, I Ketut; Mandala, Kastawan (E-Jurnal Manajemen, 2015)
The purpose of this study was to determine the effect of green marketing mix consists of product, promotion, price and place of the green product purchasing decisions at Sari Organic Restaurant Ubud. This study used a quantitative research using surveys and questionnaires to 100 visitors Sari Organic Restaurant Ubud. The data analysis technique used in this study is multiple linear regression analysis. It was found that the variable product, promotion, price and place simultaneously influence the purchasing decision of green products in Restaurant Ubud Sari Organic and variable product, promotion, price and place to have a positive and significant effect partially on green product purchasing decisions at Sari Organic Restaurant Ubud.
Keywords: Green Marketing Mix; Keputusan Pembelian